Characterization in Helicobacter pylori of a Nickel Transporter Essential for Colonization That Was Acquired during Evolution by Gastric Helicobacter Species. - Frédéric Fischer; Marie Robbe-Saule; Evelyne Turlin; Francesco Mancuso; Valérie Michel; Pierre Richaud; Frédéric J Veyrier; Hilde De Reuse; Daniel Vinella (PLoS Pathogens, 2016)
Metal acquisition is crucial for all cells and for the virulence of many bacterial pathogens. In particular, nickel is a virulence determinant for the human gastric pathogen Helicobacter pylori as it is the cofactor of two enzymes essential for in vivo colonization, urease and a [NiFe] hydrogenase. To import nickel despite its scarcity in the human body, H. pylori requires efficient uptake mechanisms that are only partially defined. Indeed, alternative ways of nickel entry were predicted to exist in addition to the well-described NixA permease. Using a genetic screen, we identified an ABC transporter, that we designated NiuBDE, as a novel H. pylori nickel transport system. Unmarked mutants carrying deletions of nixA, niuD and/or niuB, were constructed and used to measure (i) tolerance to toxic nickel exposure, (ii) intracellular nickel content by ICP-OES, (iii) transport of radioactive nickel and (iv) expression of a reporter gene controlled by nickel concentration. We demonstrated that NiuBDE and NixA function separately and are the sole nickel transporters in H. pylori. NiuBDE, but not NixA, also transports cobalt and bismuth, a metal currently used in H. pylori eradication therapy. Both NiuBDE and NixA participate in nickel-dependent urease activation at pH 5 and survival under acidic conditions mimicking those encountered in the stomach. However, only NiuBDE is able to carry out this activity at neutral pH and is essential for colonization of the mouse stomach. Phylogenomic analyses indicated that both nixA and niuBDE genes have been acquired via horizontal gene transfer by the last common ancestor of the gastric Helicobacter species. Our work highlights the importance of this evolutionary event for the emergence of Helicobacter gastric species that are adapted to the hostile environment of the stomach where the capacity of Helicobacter to import nickel and thereby activate urease needs to be optimized.